2022
DOI: 10.3389/fimmu.2022.941556
|View full text |Cite
|
Sign up to set email alerts
|

Novel macrophage-related gene prognostic index for glioblastoma associated with M2 macrophages and T cell dysfunction

Abstract: This study aims to construct a Macrophage-Related Gene Prognostic Index (MRGPI) for glioblastoma (GBM) and explore the underlying molecular, metabolic, and immunological features. Based on the GBM dataset from The Cancer Genome Atlas (n = 156), 13 macrophage-related hub genes were identified by weighted gene co-expression network (WGCNA) analysis. 5 prognostic genes screened by Kaplan-Meire (K-M) analysis and Cox regression model were used to construct the MRGPI, including GPR84, NCF2, HK3, LILRB2, and CCL18. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…22 In gastrointestinal cancer, high expression level of NCF2 was associated with the poor prognosis of esophageal squamous cell carcinoma, 23 and Zhang et al revealed that upregulation of NCF2 promoted the angiogenesis and metastasis of gastric cancer through NF-κB pathway. 24 Besides, NCF2 was selected to construct a Macrophage-Related Gene Prognostic Index for glioblastoma, 25 and methylation of CpG sites of NCF2 was associated with the risk of breast cancer. 26 However, the effect of NCF2 on the prognosis of HCC has not been explored before.…”
Section: Discussionmentioning
confidence: 99%
“…22 In gastrointestinal cancer, high expression level of NCF2 was associated with the poor prognosis of esophageal squamous cell carcinoma, 23 and Zhang et al revealed that upregulation of NCF2 promoted the angiogenesis and metastasis of gastric cancer through NF-κB pathway. 24 Besides, NCF2 was selected to construct a Macrophage-Related Gene Prognostic Index for glioblastoma, 25 and methylation of CpG sites of NCF2 was associated with the risk of breast cancer. 26 However, the effect of NCF2 on the prognosis of HCC has not been explored before.…”
Section: Discussionmentioning
confidence: 99%
“…HK3 was also identified as a biomarker of macrophages in clear cell renal cell carcinoma ( Xu et al, 2021 ). Moreover, HK3 showed an association with M2 macrophages and T cell dysfunction in GBM ( Ji et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms of this phenotype were sought to be elucidated. Since HK3 is a subtype of hexokinase involved in the first step of glucose metabolism, lactate is a direct by-product of glycolysis, which has been widely demonstrated to be directly involved in tumor progression by M2 macrophage polarization in tumor microenvironment [18,26]. Histone lysine lactylation (Kla) was identified as a novel post-modification (PTM) [27].…”
Section: Hk3 In Neuroblastoma Affects Lactate Secretion In the Microe...mentioning
confidence: 99%